Examen especial al componente inventarios y su incidencia en los estados financieros del grupo ferretero los Hidros, de Riobamba, período 2018 - Silvia Isabel, Tiumaico Silva (2020)
Grupo Ferretero Los Hidros, is located in Riobamba city, it has been in the market for more than 13 years, time in which it has dedicated itself to the commercialization of PVC pipes and accessories for drinking water systems, irrigation, sewerage, electrical networks, industrial and residential pumping systems; ironmongery items and construction materials in general. The special examination of the inventory component was applied in the Grupo Ferretero Los Hidros, corresponding to the period from January 1 to December 31, 2018, in order to determine the impact on the Financial Statements. In Chapter I the approach to the problem and the objectives were developed. In Chapter II are the investigations that have been carried out on the analyzed topic, the generalities of the Grupo Ferretero Los Hidros and the concepts that gave a better understanding to this topic. In the Chapter III establishes the research method being deductive since it allows a study to be carried out based on the global observation of inventory control. Chapter IV contains the development of the 3 phases of the Special Exam: The first phase is planning: here is the general information of the Grupo Ferretero Los Hidros, which was collected through an observation guide, interview and questionnaires. The second phase is the execution: here the internal control evaluation was carried out, resulting in a moderate level, and the work papers were prepared with the analysis of the inventories component. The third phase the communication of results: Through the Final Report, the results of Phase I and II were released, concluding that inventories are not managed properly and this affects the information presented in the financial statements not is truthful.